An air-stable artificial synapse based on a lead-free double perovskite Cs2AgBiBr6 film for neuromorphic computing. Issue 17 (16th April 2021) - Lao, Jie; Xu, Wen; Jiang, Chunli; Zhong, Ni; Tian, Bobo; Lin, Hechun; Luo, Chunhua; Travas-sejdic, Jadranka; Peng, Hui; Duan, Chun-Gang
Abstract : An Ag/PMMA/Cs2 AgBiBr6 /ITO device exhibits excellent stability and reproductivity before and after 20 days of storage in an ambient environment. The pattern recognition accuracy reaches 91.3%, which is simulated by using the MNIST dataset. Abstract : Halide perovskites (HPs) are promising materials for preparing nonvolatile memory and artificial synapse devices. However, the instability and toxicity of lead HPs seriously restrict their further application. Herein, a lead-free and air-stable Ag/polymethylmethacrylate (PMMA)/Cs2 AgBiBr6 /ITO device is fabricated, which exhibits typical resistive switching (RS) characteristics and synaptic behaviors, including long-term potentiation (LTP), long-term depression (LTD), paired-pulse facilitation (PPF) and spike-dependent plasticity. The ion migration of Br − and Ag + in Cs2 AgBiBr6 led to the formation and fracture of a conductive filament. Notably, no obvious decay in the device performance was observed after being directly exposed to the ambient environment for 20 days, indicating that the device exhibits good environmental stability. Furthermore, the recognition rate reaches 91.3% by using the MNIST handwritten data set. This air-stable and lead-free device provides a new candidate for the next generation of neuromorphic computation based on halide perovskites.